2017
DOI: 10.1016/j.jascer.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of microstructure and mechanical properties of PIP-C/SiC composites after high-temperature oxidation

Abstract: C/SiC composites had been prepared by PIP process. The evolution of microstructure and mechanical properties after high-temperature (>1500 • C) oxidation were discussed and compared. The results showed that PIP-C/SiC composites had been severely damaged after oxidation tests, micro-cracks and holes emerged along with the increasing of the oxidation temperature, which lead to the decreasing of mechanical properties. After high-temperature flexural tests, the thermal mismatch between C fibers and SiC matrix grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Figure 3(b) shows the microstructure of the S1 composite without interface, and it can be found that there is obvious interface debonding in the matrix and fiber. This is mainly due to the mismatch of thermal expansion coefficient between matrix and fiber and the volume effect of matrix cracking [ 23 ]. The S3 sample has a dense and uniform PyC interface, as shown in Figure 3(a) , and the overall microstructure of the material is relatively complete.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3(b) shows the microstructure of the S1 composite without interface, and it can be found that there is obvious interface debonding in the matrix and fiber. This is mainly due to the mismatch of thermal expansion coefficient between matrix and fiber and the volume effect of matrix cracking [ 23 ]. The S3 sample has a dense and uniform PyC interface, as shown in Figure 3(a) , and the overall microstructure of the material is relatively complete.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, researchers have conducted many investigations on its mechanical properties of C/SiC composites. They often rely on physical information released from the internal changes in materials to describe the damage process, such as electrical resistance, mechanical parameters, acoustic emission (AE) [11][12][13][14][15][16][17]. AE is defined as a phenomenon whereby transient elastic waves are generated by the rapid release of energy from a localized source or sources within a material [18].…”
Section: Introductionmentioning
confidence: 99%